Closed‐loop insulin delivery in end‐of‐life care: a case report. Issue 12 (3rd May 2019) - Boughton, C. K.; Bally, L.; Hartnell, S.; Wilinska, M.; Coll, A. P.; Evans, M.; Stettler, C.; Hovorka, R.
What's new?: Glucose management for people with diabetes approaching the end of life can be very challenging, and clinical practice is variable. We present a case where closed‐loop insulin delivery was used to manage glucose levels in an individual hospitalized during a period of terminal illness. During the time in which closed‐loop insulin delivery was used, glucose control was safe, with no glucose‐related harm. Closed‐loop systems may provide a safer and less burdensome approach to glucose management towards the end of life. Studies are needed to determine safety, efficacy and acceptability in this population. Abstract: Background: Glucose management for people with diabetes approaching the end of life can be very challenging. The aim is to balance a minimally invasive approach with avoidance of symptomatic hypo‐ and hyperglycaemia. Case report: We present a case of a hospitalized individual whose glucose was managed with closed‐loop insulin delivery within a randomized controlled trial setting during a period of terminal illness. During the time in which closed‐loop insulin delivery was used, glucose control was safe, with no glucose‐related harm. The mean ± sd sensor glucose for this individual was 11.3 ± 4.3 mmol/l, percentage of time spent in target glucose range between 6 and 15 mmol/l was 70.5%, time spent in hypoglycaemia was 2.0% and time spent in significant hyperglycaemia >20 mmol/l was 2.6%. Conclusion: Closed‐loop systems can accommodate personalized glucose targets and highly variable insulin requirements. Factory‐calibrated continuous glucose sensors and insulin pump therapy are less intrusive than finger‐stick glucose measurements and insulin injections, respectively. Closed‐loop systems may provide a safer and less burdensome approach to glucose management towards the end of life.